Modification of Maternal Sleep Position to Optimise Fetal Well‐being in Late Pregnancy: A Survey in a Multicultural New Zealand Region. (19th September 2017) - Cronin, Robin S.; Chelimo, Carol; Mitchell, Edwin A.; Okesene‐Gafa, Kara; Thompson, John; Taylor, Rennae S.; Hutchison, B. Lynne; McCowan, Lesley M.E.
Abstract : Purpose: This survey investigated late pregnancy maternal sleep practices and ability to modify sleep position in order to generate information on which to base future public health messages about optimal going‐to‐sleep position. Research Question: What are the sleep practices of women in late pregnancy, and what are their views about changing going‐to‐sleep position if this was recommended? Significance: Maternal sleep position in late pregnancy is a modifiable risk factor for late stillbirth. A 2011 study from Auckland, New Zealand, was the first to demonstrate a 2‐fold increased risk for women who did not go to sleep on their left side the night before the fetus was thought to have died, with the highest risk for women who settled to sleep supine. This association has since been confirmed by an Australian and Ghanaian study and a New Zealand multicentre study. Methods: A random sample of ethnically‐representative women (N = 377), between 28 and 42 weeks' gestation, were surveyed in 2014 in South Auckland, New Zealand, a multicultural and socioeconomically disadvantaged population with an increased risk of stillbirth. Factors independently associated with non‐left side going‐to‐sleep position in late pregnancy were identified using multivariable logistic regression. Results: Self‐reported going‐to‐sleep position in the last week was left (30%), right (22%), supine (3%), either side (39%), and other (6%). The majority (68%) had received advice about pregnancy sleep position. A non‐left position was more likely to be reported by women of Maori (adjusted odds ratio [aOR], 2.64; 95% confidence interval [CI], 1.23‐5.66) or Pacific (aOR, 2.91; 95% CI, 1.46‐5.78) ethnicity, and those who did not sleep on the left‐hand side of the bed (aOR, 3.29; 95% CI, 2.03‐5.32). Most (87%) non‐left sleepers reported that they would have minimal difficulty changing to going to sleep on their left side in late pregnancy if this was better for their fetus. Discussion: The results from this survey suggest that going‐to‐sleep position in late pregnancy is likely to be readily modifiable. This suggests that a public health intervention, about the importance of optimal late pregnancy going‐to‐sleep position to optimise fetal well‐being, is likely to be feasible in similar communities with an increased risk of stillbirth.